The Use of Language Variation in Social Media: A Review of Sociolinguistic Literature - Wahyudiantari, Ni Wayan Prami (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The emergence of technology brings the presence of social media, which has become a platform for long-distance communication for many people today. Through social media, many people with different characteristics can meet, including the characteristics of the language they use. This can be caused by various factors, ranging from geographical differences, gender, to daily habits. Through this research, the researcher aims to find out the language variation in social media. The method used by researchers is the literature review method. The data in this research is previous research as many as 5 relevant articles. The results of the research have shown that language variation in social media is influenced by gender, age, cultural identity, and individual characteristics themselves. The literature reviewed in this study provides insights into language variation in social media.